Mechanisms of current passage and excitation of electroluminescence in GaSe:Er monocrystals - Tagiyev, B.G.; Madatov, R.S.; Aydayev, F.Sh.; Abbasova, T.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The paper deals with electroluminescence investigations in GaSe:Er monocrystals. It is ascertained that Er³⁺ centers in GaSe are excited by two ways: a) as a result of non-radiating recombination of the injected charge carrier in donor-acceptor states and, b) transfer of evolved energy by means of Coulomb interaction. The concentration of majority carriers in the current step field (6.26•10¹¹ cm⁻³) and activation energy of impurities (0.14 eV) have been determined using data obtained.